Coronavirus Disease (COVID-19) Associated Rhinocerebral Mucormycosis and Complications: A Case Report - Al Osta, Soad; Atwi, Gibran; El Ahmar, Nourhan; Bejjani, Noha; Abillama, Fayez; Matli, Kamal (International Journal of Clinical Research, 2021)
Background: Mucormycosis is a rare fatal infection caused by a ubiquitous fungus from the order of Mucorales, which can have varying clinical presentations. Immunocompromised patients are particularly susceptible to mucormycosis and can suffer fatal consequences if not treated adequately. COVID-19 infection with its immunomodulatory properties has been associated with a wide range of secondary bacterial and fungal infections. We present a case of rapidly progressive rhinocerebral mucormycosis post-COVID-19 infection with the subsequent development of several complications associated with the disease. Case Report: A 62-year-old male patient with a history of hypertension and diabetes mellitus type II, presented 14 days post-COVID-19 recovery with right facial swelling, erythema, and right eye proptosis. Throughout his disease, the patient developed blindness and cranial nerve palsies. He was also found to have palatal necrotic lesions, consistent with the diagnosis of mucormycosis. The patient’s disease was complicated by Garcin syndrome, meningitis, orbital apex syndrome, cavernous sinus thrombosis, brain infarction, and hemorrhage. Despite all measures and interventions, the patient died. Conclusion: COVID-19 infection and its treatments are associated with an increased risk of secondary fungal infections like mucormycosis. As such, a high index of suspicion is needed amongst healthcare workers for the early diagnosis and treatment of such opportunistic infections since prompt treatment is associated with a marked improvement in outcome. Furthermore, optimal glucose control and judicious use of corticosteroids in COVID-19 patients decreases the risk of developping such life threatening superinfections.